Answer:
The second one
Step-by-step explanation:
......................
Answer:
23
Step-by-step explanation:
Answer:
4 flights of stairs in 5 minutes
Step-by-step explanation:
8/10 times 5
Answer:
The solution for the system of equations is
x=2,y=−2
Explanation:
4x−3y=14.....equation (1)
y=−3x+4.....equation (2)
Solving by substitution
Substituting equation 2 in equation 1
4x−3⋅(−3x+4)=14
4x+9x−12=14
13x=14+12
13x=26
x=2
Finding y by substituting x in equation 1
4x−3y=14
4⋅2−3y=14
8−3y=14
8−14=3y
3y=−6
y=−2
|DF| = |DE| + |EF| |DF| = 9x -36 |DE| = 47 |EF| = 3x+10 Substitute: 9x - 39 = 47 + 3x + 10 9x - 39 = 3x + 57 |+39 9x = 3x + 96 |-3x 6x = 96 |:6 x = 16 Put the value of x to the equation |EF| = 3x + 10 |EF| = (3)(16) + 10 = 48 + 10 = 58 Answer: |EF| = 58
Read more at Answer.Ya.Guru – https://answer.ya.guru/questions/4046336-if-df-9x-39-find-ef.html